The Impact of Implementing the Requirements of Governance on the Performance of the Teaching Staff Members at the University of Jeddah - Zatar, Tayseer Said (International Review of Management and Marketing, 2019)
The aim of this study is to find out the effect of the implementation of governance requirements (justice, equality, transparency, clarity, accountability) on the performance of teaching staff members at the University of Jeddah, Saudi Arabia. The study reached a number of results. The most important of which is the existence of a statistically significant impact on governance on the performance of faculty members at the University of Jeddah. In some aspects including activating the role of the media in spite of its importance in the universities. In addition, the lack of granting freedom of opinion and expression for faculty members. In addition, lack of participation of faculty members in the major decisions related to the university’s academic plans, as well as not giving the creators of scientific research material and moral incentives. The study recommended that senior management in Saudi universities at all levels of management, should take care of the requirements of governance in their work, especially with regard to fairness, equality, transparency, clarity and accountability by issuing clear laws and regulations and activating the role of the media and freedom of opinion and expression. The university has a great role in improving the performance of faculty members. Keywords: Governance, Justice and Equality, Transparency, Clarity, accountability, teaching staff performance JEL Classification: I23 DOI: https://doi.org/10.32479/irmm.7466